Análise dos fatores determinantes para a ocorrência de ociosidade das redes de esgoto sanitário no município de Caxias do Sul - RS - Suita, Maria do Carmo Antunes (My University, 2018)
In the current model of investment in sanitary sewage, the highest say respect to works in sewage treatment plants and in the implantation of networks, which will often not receive the connection of users. In Brazil, the percentage of users connected to the sewage collection system is low, since the land connection, at the user's responsibility, not performed. In this way, less sewage reaches the stations and a smaller quantity is treated. The municipality of Caxias do Sul is following this observation, because despite large investments in sewage systems, it has only 37.05% as an indicator of treated sewage (SNIS, 2015). The objective of this study is to analyze the determinants of the occurrence of idleness of sanitary sewage networks in this Municipality. For that, an exploratory and quantitative research it was made, through the application of questionnaires to two publics: together with the employees of the sanitation company and with the residents of the neighborhood selected as sampling. Documentary research and direct observation with the company and its sewage connection system were also carried out. As a result it was verified that the idleness of the networks is an unknown problem of the residents and collaborators. The lack of information about the sewage system, not wanting to damage the floor, the value of the connection were reasons pointed out by the residents, the employees added, lack of stimulation, lack of penalties, downside, and the claim to be very laborious make the call. The legislation is unknown by the residents, there is no control of the sanitation company on unconnected connections, which charges tiered tariff for network availability and treatment. Obstacles that can be solved by the Municipality through structuring measures: management, regulation, environmental education programs, and adequacy of procedures, as raised in the research and listed as recommendations. The study confirmed the need for the valuation of sewage services in the universalization of sanitation.
No modelo atual de investimento em esgotamento sanitário, os maiores custos dizem respeito às obras em estações de tratamento de esgotos e à implantação de redes que, muitas vezes, não receberão a conexão dos usuários. No Brasil, o percentual de usuários conectados à rede coletora de esgoto é baixo, pois a ligação predial, de responsabilidade do usuário não é realizada. Dessa forma, menos esgoto chega às estações e uma quantidade menor é tratada. O município de Caxias do Sul acompanha essa constatação, pois apesar de grandes investimentos em sistemas de esgotos, tem apenas 37,05% como indicador de esgoto tratado por volume de água consumida (SNIS, 2015). A realização do presente trabalho tem como objetivo analisar os fatores determinantes da ocorrência de ociosidade das redes de esgotamento sanitário nesse Município. Para tanto, foi realizada pesquisa exploratória e quantitativa, por meio da aplicação de questionários a dois públicos: junto aos colaboradores da empresa de saneamento e junto aos moradores do bairro selecionado como amostragem. Também foi realizada pesquisa documental e observação direta junto à empresa e seu sistema de ligação de esgoto. Como resultado foi verificado que a ociosidade das redes é um problema desconhecido dos moradores e colaboradores. A falta de informação sobre o sistema de esgoto, não querer danificar o piso, o valor da conexão foram motivos apontados pelos moradores. Os colaboradores acrescentaram a falta de estímulo, a inexistência de sanções, caimento contrário, e a alegação de ser muito trabalhoso fazer a ligação. A legislação é desconhecida pelos moradores, não há controle da empresa de saneamento sobre as ligações não conectadas, que cobra tarifa pela disponibilidade de rede e tratamento. Entraves que podem ser solucionados pelo Município por meio de medidas estruturantes: de gestão, regulamentação, programas de educação ambiental, e adequação de procedimentos, conforme levantados na pesquisa e elencados como recomendações. O estudo confirmou a necessidade da valoração dos serviços de ligações de esgoto na universalização do saneamento.
Keywords: Esgotos - Caxias do Sul (RS); Águas residuais - Purificação; Saneamento; Sewerage - Caxias do Sul (Brazil); Sewage -Purification; Sanitation